The role of information systems in decision-making: a field study at the company Sonatrach, Skikda - thligia, Noua; Boughlita, Ilham (Dirassat Journal Economic Issue, 2013)
The institution is considered as a center for decision-making in order to be able to achieve its goals and continuity, and therefore it needs information that is a basis and support for making decisions as one of the most important resources available in any institution, and this is only achieved through an effective information system.